Setting an Agenda for Entrepreneurial Governments: A Global Baseline Assessment of Disaster Risk Reduction Investment - Paunga, Fakatava; Lassa, Jonatan A. (TDMRC, Universitas Syiah Kuala, 2020)
Disaster scholars and practitioners have argued that disaster risk reduction (DRR) is a legitimate investment and there are multiple dividends that are associated with DRR. This paper argues that there is a need for a new policy framing that DRR investment is imperative that will generate dividends for governments and society at large. Under the auspice of the Sendai Framework for disaster risk reduction, governments around the world and international communities are urged to develop DRR strategies to not only aimed at reducing mortality and disaster losses but also provide multiple benefits to the society including achieving Sustainable Development Goals. This research aims to develop a global scale baseline of investment in disaster risk reduction worldwide. A total of 222 countries and territories are included in this study to assess their relative investment in DRR. We define DRR investment as an aggregation of three distinct investment: financial investment, social investment and early warning system investment. The study generated a global index that measures disaster risk reduction investment committed by the countries. The findings suggest that investment in disaster risk reduction remains low in high risk but low to middle - income countries in contrast to higher income countries such as the OECD group. Insights from our research suggests that the concept of entrepreneurial government is needed in order to be more ambitious in triggering, facilitating and initiating investment in disaster risk reduction in a broader framework.